TREATMENT OF OSTEOPOROSIS: CLINICAL EXPERIENCE IN USING A GENERIC DRU - Nataliya Vladimirovna Toroptsova; O A Nikitinskaya; Nataliya Vladimirovna Toroptsova; O A Nikitinskaya (Современная ревматология, 2011)
Interest has recently been aroused in generic drugs because of the reduction of government expenditures on treatment. These drugs must meet the same standards of quality, effectiveness, and safety as those for original medicines. The paper discusses the concepts of biological and pharmaceutical drug equivalence, which permit original and generic drugs to be equalized in rights. Bioequivalence is considered using as an example alendronate that is extensively used to treat osteoporosis.